Trade policy uncertainty - Duan, Chenchen (Kansas State University, 2019)
China has experienced tremendous growth in its exports to the world since the 1990’s. Its exports to the world rose from just 2 percent of the world’s share to close to 13 percent from 1990 to 2017. Its exports to the United States increased even more during the same period, from 3 percent to 33 percent. China’s WTO accession, awarding China permanent most favored nation (MFN) status, led to this dramatically increase in exports through a reduction in the US trade policy uncertainty (TPU). This report first reviews the sources of gains from trade and the gravity equation to estimate trade flow between countries. Second, this report illustrates why optimal tariffs are not zero and the effects of tariffs on trade volumes and import prices. TPU arises when countries have the power to increase tariffs. This report reviews the recent literature on the effects of reducing TPU on export growth, export prices, and product varieties. Handley and Limão (2017a) find that over one third of the export growth from China to U.S. after China’s accession to the WTO is accounted by the reduction in TPU between China and US.
Keywords: Trade policy; Uncertainty; Tariff